Protective film and structure
By using the protective layer and bonding layer of polyolefin resin in the protective film, the performance reduction of the performance caused by the degradation of polyurethane resin has been solved, and good followability and durability of a variety of surface shapes are realized.
Patent Information
- Application Number
- CN202380049462.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-01
- Filing Date
- 2023-07-03
- Publication Date
- 2025-01-28
AI Technical Summary
Due to the deterioration of the polyurethane resin over the years, the performance of the existing protective film is degraded, making it difficult to effectively protect structures of various surface shapes for a long time.
The protective layer containing polyolefin resin and the bonding layer configured on the protective layer. The stretching load when 10 % elongation is except for the elongation of 10 % elongation. , Improve the softness and durability of the protective film.
The good followability and durability of a variety of surface shapes are realized, the phenomenon of degradation is reduced, and the service life of the protective film is prolonged.
Smart Images

Figure CN119384356A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to protective films and structures. Background Art
[0002] Structures installed outdoors or used outdoors are exposed to ultraviolet rays of sunlight, wind, rain, snow, sleet, hail, thunder, seawater, fog, sand, dust, dust, etc. In addition, the above structures are also affected by the impact of birds and flying objects. In this way, the above structures are in a harsh environment, and therefore, due to long-term use, they may suffer from unfavorable conditions such as damage, deformation, surface contamination, and surface peeling.
[0003] Therefore, in order to protect the structure, a technology of attaching a protective film to the surface of the structure has been proposed. For example, Patent Document 1 discloses a protective film for automobile exterior packaging, etc. In addition, Patent Document 2 discloses a protective film for wind turbine blades of a wind power generation device.
[0004] Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2010-260942 Patent Document 2: International Publication No. 2012 / 102294 Summary of the invention
[0005] Technical problem to be solved by the invention Since structures have various three-dimensional shapes, it is desirable that a protective film can be attached to conform to various surface shapes.
[0006] Patent Document 1 discloses a protective film made of a polyurethane resin having a tensile elongation at break of 120% or more at 80°C and / or a gloss retention of 80% or more after 2 years of outdoor exposure. It is believed that such a protective film can be attached to various surface shapes, has good followability to various surface shapes, such as curved surfaces, and has excellent durability after attachment.
[0007] However, polyurethane resins are prone to deterioration over time, and therefore, protective films made of polyurethane resins have a problem of performance degradation due to deterioration over time.
[0008] The present invention has been made in view of the above circumstances, and a main object of the present invention is to provide a protective film that has good conformability to various surface shapes, such as curved surfaces and irregularities, and is less likely to deteriorate over time.
[0009] Technical solutions for solving technical problems One embodiment of the present invention provides a protective film comprising a protective layer made of a polyolefin resin and an adhesive layer disposed on one surface of the protective layer, wherein the value obtained by dividing the tensile load at 10% elongation by the elongation at 10% elongation is 3.0 N / mm or less.
[0010] Another embodiment of the present invention provides a structure having the above-mentioned protective film.
[0011] Effects of the Invention The present invention can provide a protective film that has good conformability to various surface shapes, such as curved surfaces and irregularities, and is less likely to deteriorate over time. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a schematic cross-sectional view illustrating the protective film of the present invention.
[0013] Figure 2 This is a schematic cross-sectional view illustrating the protective film of the present invention. DETAILED DESCRIPTION
[0014] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings, etc. However, the present invention can be implemented in a large number of different ways and is not limited to the description of the embodiments illustrated below. In addition, in the accompanying drawings, in order to explain more clearly, the width, thickness, shape, etc. of each part are sometimes schematically indicated compared to the actual method, which is only used as an example and is not intended to limit the interpretation of the present invention. In addition, in this specification and the accompanying drawings, for the figures that have appeared, the same symbols are sometimes marked for the same elements as the aforementioned elements, and the detailed description is appropriately omitted.
[0015] In this specification, sometimes it is expressed as a method of arranging other components on a certain component. When simply marked as "upper" or "lower", unless otherwise specified, it includes two cases: a case where other components are arranged directly above or directly below a certain component in a manner of contacting with the certain component, and a case where other components are arranged further above or below a certain component via another component. In addition, in this specification, sometimes it is expressed as a method of arranging other components on the surface of a certain component. When simply marked as "surface side" or "surface", unless otherwise specified, it includes two cases: a case where other components are arranged directly above or directly below a certain component in a manner of contacting with the certain component, and a case where other components are arranged further above or below a certain component via another component.
[0016] In addition, in this specification, a member called a "sheet" is also included in a "film".
[0017] Hereinafter, the protective film and the structure in the present invention will be described in detail.
[0018] A. Protective film The protective film of the present invention comprises a protective layer comprising a polyolefin resin and an adhesive layer disposed on one surface of the protective layer, wherein the value obtained by dividing the tensile load at 10% elongation by the elongation at 10% elongation is 3.0 N / mm or less.
[0019] In this specification, for ease of description, “a value obtained by dividing the tensile load at 10% elongation by the elongation at 10% elongation” may be simply referred to as “a spring constant at 10% elongation”.
[0020] Figure 1 This is a schematic cross-sectional view illustrating the protective film of the present invention. Figure 1 The protective film 10 in the embodiment includes a protective layer 1 made of a polyolefin-based resin and an adhesive layer 2 disposed on one surface of the protective layer 1. The spring constant of the protective film 10 at 10% elongation is equal to or less than a predetermined value.
[0021] Here, as an existing protective film, it is known to use a polyurethane resin as described in Patent Document 1. However, polyurethane resins tend to decompose slowly with long-term use, and there is a possibility that the performance of the protective film will decrease due to degradation over time. In the present invention, since a polyolefin resin is used in the protective layer of the protective film, such an undesirable situation can be suppressed. In addition, the inventors of the present invention conducted a study and found that, as described in the embodiment column described later, a protective film having a protective layer containing a polyolefin resin is less likely to deteriorate over time (hereinafter sometimes referred to as having good durability) than a protective film having a protective layer containing a polyurethane resin.
[0022] In addition, in the present invention, since the spring constant of the protective film at 10% elongation is less than a predetermined value, the flexibility of the protective film is good, and thus the ability to follow curved surfaces and irregularities can be improved.
[0023] Therefore, the protective film of the present invention has excellent followability to curved surfaces and irregularities and durability, and is therefore suitable as a protective film for structures installed outdoors or used outdoors.
[0024] In addition, it is important to perform regular inspections, repairs when necessary, and maintenance such as replacement of parts for structures. In the present invention, the protective film has good flexibility, so not only is the construction performance good when the protective film is attached to the surface of the structure, but the construction performance is also good when the protective film is peeled off from the surface of the structure when the protective film is replaced. In addition, in the present invention, since the protective film has good durability, it is possible to suppress peeling defects caused by deterioration of the protective film.
[0025] Hereinafter, each structure of the protective film in the present invention will be described.
[0026] 1. Physical properties of protective film (1) Spring constant at 10% elongation In the protective film of the present invention, the spring constant at 10% elongation is 3.0 N / mm or less, preferably 0.1 N / mm or more and 2.5 N / mm or less, and more preferably 0.5 N / mm or more and 1.5 N / mm or less. By making the spring constant of the protective film below a predetermined value, the followability to curved surfaces and uneven surfaces can be improved. On the other hand, if the spring constant of the protective film is too small, it becomes too soft and the protective film may become difficult to handle.
[0027] Here, the spring constant is the value obtained by dividing the tensile load (N) by the elongation (mm). The spring constant at 10% elongation is the value obtained by dividing the tensile load (N) at 10% elongation by the elongation (mm) at 10% elongation. In the tensile test described later, when the distance between the clamps is 100mm, the elongation at 10% elongation becomes 10mm. Therefore, the spring constant at 10% elongation becomes the value obtained by dividing the tensile load (N) at 10% elongation by the elongation (10mm) at 10% elongation.
[0028] The spring constant is obtained by performing a tensile test according to ISO 527-3: 2018 and measuring the tensile load and elongation. Specific measurement conditions of the tensile test are as follows. As a tensile testing machine, for example, "Tensilon RTF1150" manufactured by A & D Corporation can be used.
[0029] (Measurement conditions for tensile test) Test piece: long strip Test piece size: width 10mm, length 120mm Distance between fixtures: 100mm Stretching speed: 50mm / min Measurement temperature: 25℃ When the protective film has a diaphragm, the spring constant refers to the spring constant of the protective film excluding the diaphragm.
[0030] (2) Tensile failure stress In the protective film of the present invention, the maintenance rate of the tensile stress after the light resistance test described below is preferably 18% or more, more preferably 19% or more, and further preferably 20% or more. In addition, the maintenance rate of the tensile stress may be 60% or more, 70% or more, or 80% or more. By making the maintenance rate of the tensile stress within the above range, the durability of the protective film can be improved. Within the above range, poor peeling caused by deterioration of the protective film can be suppressed, and the workability when peeling the protective film is also good.
[0031] (Lightfastness test) In the light resistance test, the irradiance is 1000W / m 2 , irradiate with ultraviolet light with a wavelength of 300nm to 400nm for 240 hours at a blackboard temperature of 63°C. When the protective film has a diaphragm, peel off the diaphragm, and adhere an ETFE (ethylene-tetrafluoroethylene copolymer) film with a thickness of 75μm to the surface of the adhesive layer side, and then perform a light resistance test. In addition, in the light resistance test, ultraviolet light is irradiated from the surface of the protective layer side of the protective film. As a light source, a metal halide lamp can be used. In addition, it can be considered that the 240 hours in the above light resistance test is equivalent to 10 years of outdoor exposure, so the irradiation time is set to 240 hours.
[0032] The maintenance rate of the tensile breaking stress after the light resistance test was calculated by the following formula (1).
[0033] Maintenance rate of tensile stress after light resistance test (%) = tensile stress after light resistance test / tensile stress before light resistance test × 100 (1) In the protective film of the present invention, the maintenance rate of the tensile stress after the high temperature and high humidity test described below is preferably 35% or more, more preferably 37% or more, further preferably 40% or more, and particularly preferably 70% or more. By setting the maintenance rate of the tensile stress to the above range, the durability of the protective film can be improved. When it is within the above range, the peeling failure caused by the deterioration of the protective film can be suppressed, and the workability when peeling the protective film is also good.
[0034] (High temperature and high humidity test) In the high temperature and high humidity test, the film was stored at 85°C and 85%RH for 2000 hours. If the protective film had a separator, the separator was peeled off and a 75 μm thick ETFE (ethylene-tetrafluoroethylene copolymer) film was attached to the adhesive layer side before the high temperature and high humidity test.
[0035] The maintenance rate of the tensile breaking stress after the high temperature and high humidity test was calculated by the following formula (2).
[0036] Maintenance rate of tensile stress after high temperature and high humidity test (%) = tensile stress after high temperature and high humidity test / tensile stress before high temperature and high humidity test × 100 (2) In the protective film of the present invention, the initial tensile stress, i.e., the tensile stress before the test is preferably 10 MPa to 40 MPa, more preferably 13 MPa to 40 MPa, and further preferably 15 MPa to 40 MPa. If the tensile stress is too high, the protective film becomes difficult to stretch, and the ability to follow curved surfaces and uneven surfaces may be reduced. In addition, if the tensile stress is too low, the strength and durability may be reduced.
[0037] In addition, the tensile breaking stress of the protective film means the tensile breaking stress in the MD direction.
[0038] In addition, the MD direction refers to the flow direction of the protective layer during film formation, and the TD direction refers to the direction perpendicular to the MD direction. For example, when the protective film is in a long strip shape, the MD direction refers to the length direction of the protective film, and the TD direction refers to the width direction of the protective film.
[0039] Here, the tensile breaking stress can be measured in accordance with ISO 527-3: 2018. Specific measurement conditions are as follows. As a tensile testing machine, for example, "Tensilon RTF1150" manufactured by A & D Corporation can be used.
[0040] (Measurement conditions) Test piece: long strip Test piece size: width 10mm, length 50mm Distance between fixtures: 30mm Stretching speed: 50mm / min Measurement temperature: 25℃ In addition, when the protective film has a diaphragm, the tensile fracture stress refers to the tensile fracture stress of the protective film without the diaphragm. Before the above-mentioned light resistance test or high temperature and high humidity test, the tensile test is performed after the diaphragm is peeled off from the protective film. In addition, after the above-mentioned light resistance test or high temperature and high humidity test, the tensile test is performed after the ETFE film is peeled off.
[0041] (3) Yellowing degree In the protective film of the present invention, the yellowing degree (ΔYI) after the light resistance test is preferably 10 or less, more preferably 8 or less, and further preferably 5 or less. Here, as described above, it is important to perform regular inspections, repairs when necessary, and maintenance of parts such as replacement of parts for the structure. When the ΔYI is within the above range, the transparency of the protective film can be maintained. Therefore, the surface of the structure can be visually confirmed through the protective film, and therefore, the replacement period of the protective film can be easily determined.
[0042] Furthermore, polyurethane resins are prone to yellowing, and therefore conventional protective films using polyurethane resins tend to have a large ΔYI, which may make it difficult to visually check the surface of a structure through the protective film.
[0043] In addition, ΔYI after the light resistance test was calculated by the following formula (5).
[0044] ΔYI after light resistance test = yellowness after light resistance test (YI1) - yellowness before light resistance test (YI0) (5) In addition, in the protective film of the present invention, the yellowing degree (ΔYI) after the high temperature and high humidity test is preferably 10 or less, more preferably 8 or less, and further preferably 5 or less. When the ΔYI is within the above range, the transparency of the protective film can be improved. Therefore, the surface of the structure can be visually confirmed through the protective film, and therefore, the replacement period of the protective film can be easily determined.
[0045] In addition, ΔYI after the high temperature and high humidity test was calculated by the following formula (6).
[0046] ΔYI after high temperature and high humidity test = yellowness after high temperature and high humidity test (YI2) - yellowness before high temperature and high humidity test (YI0) (6) In addition, in the protective film of the present invention, the yellowness after the above test is preferably, for example, 15 or less, more preferably 8 or less, and further preferably 5 or less. When the yellowness after the above test is within the above range, the transparency of the protective film can be maintained even after the above test. Therefore, the surface of the structure can be visually confirmed through the protective film, and therefore, the replacement period of the protective film can be easily determined.
[0047] Here, the yellowness of the protective film can be determined by a stimulus value direct reading method in accordance with ISO 17223: 2014. Specific measurement conditions are as follows. As a colorimeter, for example, "CC-i" manufactured by Suga Test Instruments Co., Ltd. can be used.
[0048] (Measurement conditions) Light source: C light source Field of view: 2° In addition, when the protective film has a separator, the above yellowness refers to the yellowness of the protective film without the separator. The yellowness is measured after the separator is peeled off from the protective film before the above light resistance test or before the high temperature and humidity test. In addition, the yellowness is measured after the ETFE film is peeled off after the above light resistance test or after the high temperature and humidity test.
[0049] (4) Total light transmittance In the present invention, the total light transmittance of the protective film is, for example, preferably 80% or more, more preferably 83% or more, and even more preferably 85% or more. When the total light transmittance is within the above range, the transparency is good.
[0050] Here, the total light transmittance can be measured in accordance with ISO 13468-1:1996.
[0051] 2. Protective layer The protective layer of the present invention is a member containing a polyolefin resin. In addition, the most preferable protective layer is a member whose constituent material, excluding additives, is 100% polyolefin resin.
[0052] (1) Material of protective layer (a) Polyolefin resin Examples of the polyolefin resin include polyethylene resins and polypropylene resins, among which polyethylene resins are preferred.
[0053] Polyethylene resins include not only common polyethylene obtained by polymerizing ethylene, but also copolymers of ethylene and α-olefins. α-olefins are preferably α-olefins having a carbon number of 3 or more and 12 or less. Specifically, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-heptene, 4-methyl-pentene-1, 4-methyl-hexene-1, and 4,4-dimethylpentene-1 can be listed. α-olefins can be used alone or in combination of two or more. Among them, α-olefins without branches are preferred, and α-olefins without branches having a carbon number of 3 or more and 8 or less are more preferred. Specifically, 1-propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, and 1-octene can be listed. By making the carbon number of the α-olefin 3 or more and 8 or less, good flexibility can be imparted, and good strength can be imparted.
[0054] Specific examples of the copolymer of ethylene and α-olefin include ethylene-propylene copolymer, ethylene-1-butene copolymer, ethylene-1-hexene copolymer, ethylene-1-octene copolymer, and ethylene-4-methyl-pentene-1 copolymer.
[0055] Examples of polyethylene resins include high-density polyethylene (HDPE), low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), metallocene linear low-density polyethylene (M-LLDPE), and ultra-low-density polyethylene (VLDPE). The polyethylene resins may be used alone or in combination of two or more.
[0056] Among them, low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), metallocene linear low-density polyethylene (M-LLDPE), and ultra-low-density polyethylene (VLDPE) are preferred in view of good flexibility, transparency, and processability.
[0057] Metallocene linear low-density polyethylene (M-LLDPE) is synthesized using a metallocene catalyst as a single-site catalyst. In such polyethylene, the side chains are less branched and the monomers are evenly distributed. Therefore, the molecular weight distribution can be narrow and the density can be low, which can give flexibility and strength. In addition, the crystallinity distribution is narrow and the crystal size is uniform, so not only does it not exist with large crystal size, but the crystallinity itself is low due to the low density. Therefore, it has excellent transparency.
[0058] The lower limit of the density of the polyethylene resin is not particularly limited, but is preferably 0.870 g / cm 3 The upper limit of the density of the polyethylene resin is not particularly limited, but is preferably 0.930 g / cm 3 Below, more preferably 0.925 g / cm 3 Below, more preferably 0.920 g / cm 3 By setting the density of the polyethylene resin to be within the above range, the flexibility, transparency and processability can be improved.
[0059] Here, the density of the polyethylene-based resin can be measured by, for example, a pycnometer method in accordance with ISO 1183:2019.
[0060] The lower limit of the melting point of the polyethylene resin is not particularly limited, for example, preferably 50°C or more. The upper limit of the melting point of the polyethylene resin is not particularly limited, for example, preferably 135°C or less, more preferably 130°C or less, and further preferably 125°C or less. When the melting point of the polyethylene resin is too high, it is sometimes necessary to increase the heating temperature during molding, so there is a concern about increased manufacturing costs. On the other hand, when the melting point of the polyethylene resin is too low, there is a concern about melting in the use environment.
[0061] Here, in this specification, the melting point of a resin is measured by differential scanning calorimetry (DSC) in accordance with ISO 3146: 2000. In this case, when there are two melting point peaks, the higher temperature is taken as the melting point.
[0062] The melt flow rate (MFR) of the polyethylene resin at a temperature of 190°C is, for example, preferably 1 g / 10 minutes or more and 30 g / 10 minutes or less, more preferably 1 g / 10 minutes or more and 25 g / 10 minutes or less, and further preferably 1 g / 10 minutes or more and 20 g / 10 minutes or less. By making the MFR of the polyethylene resin below a predetermined value, the strength can be improved. In addition, by making the MFR of the polyethylene resin within the above range, the film-forming property and the softness can be improved.
[0063] Here, the melt flow rate (MFR) of the polyethylene resin can be measured in accordance with ISO 1133-1: 2011. The measurement conditions are A method, temperature 190° C., and load 2.16 kg.
[0064] In addition, the polyolefin resin may be a cross-linked polyolefin resin or a non-cross-linked polyolefin resin. In addition, the polyethylene resin may be a cross-linked polyethylene resin or a non-cross-linked polyethylene resin. Both the cross-linked type and the non-cross-linked (thermoplastic) type can exert the effect of the present invention.
[0065] In addition, the cross-linked polyolefin resin refers to a cross-linked polyolefin resin, that is, a polyolefin resin having a cross-linked bond. On the other hand, the non-cross-linked polyolefin resin refers to a polyolefin resin without a cross-linked bond. The cross-linked bond can be determined by measuring the gel fraction.
[0066] In addition, the cross-linked polyethylene resin refers to a cross-linked polyethylene resin, that is, a polyethylene resin having a cross-linked bond. On the other hand, the non-cross-linked polyethylene resin refers to a polyethylene resin that is not cross-linked.
[0067] As a crosslinking method for crosslinking the polyolefin resin, a common crosslinking method can be applied, for example, a crosslinking method using a crosslinking agent and a crosslinking method using ionizing radiation irradiation can be mentioned. Among them, a crosslinking method using a crosslinking agent is preferred.
[0068] As the crosslinking agent, a common crosslinking agent can be used, for example, an organic peroxide can be cited. As the organic peroxide, for example, peroxycarbonates, peroxyketals, and dialkyl peroxides can be cited. As peroxycarbonates, for example, tert-amyl peroxy-2-ethylhexyl carbonate and tert-butyl peroxy-2-ethylhexyl carbonate can be cited. As peroxyketals, for example, n-butyl-4,4-di(tert-butyl peroxy)valerate, ethyl-3,3-di(tert-butyl peroxy)butyrate, and 2,2-di(tert-butyl peroxy)butane can be cited. As dialkyl peroxides, for example, di-tert-butyl peroxide, tert-butyl cumyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butyl peroxy)hexane, and 2,5-dimethyl-2,5-di(tert-butyl peroxy)hexyne-3 can be cited. The crosslinking agent can be used alone or in combination of two or more.
[0069] The content of the crosslinking agent in the resin composition used for forming the protective layer can be appropriately selected depending on the target crosslinking degree and the like.
[0070] In addition, in the crosslinking method using a crosslinking agent, a crosslinking aid can be used. By using a crosslinking aid, a moderate crosslinking reaction can be promoted. In addition, since the crosslinking aid reduces the crystallinity of the polyolefin resin, transparency can be maintained. As the crosslinking aid, a common crosslinking aid can be used, for example, a multifunctional monomer having a polymerizable functional group can be cited.
[0071] Among them, from the viewpoint of improving reactivity, the crosslinking aid is preferably a urate ring-containing compound having two or more polymerizable functional groups in one molecule.
[0072] In the crosslinking aid, the number of polymerizable functional groups is preferably 2 or more in one molecule as a lower limit. On the other hand, it is preferably 6 or less, more preferably 3 or less in one molecule as an upper limit. When the number of polymerizable functional groups is too small, the crosslinking density may not be sufficiently increased. On the other hand, when the number of polymerizable functional groups is too large, the protective layer after crosslinking treatment may become brittle, which may have an adverse effect on the physical properties of the protective layer.
[0073] The polymerizable functional group is not particularly limited as long as it can react with the polyolefin resin as the base resin to impart a crosslinked structure, and among them, a group having a carbon-carbon double bond, an epoxy group, etc. are preferred. Examples of the group having a carbon-carbon double bond include a vinyl group, a (meth)acryloyl group, a (meth)acryloyloxy group, and an allyl group.
[0074] As a crosslinking aid, for example, polyallyl compounds, poly(meth)acryloyloxy compounds, and epoxy compounds can be cited. As polyallyl compounds, for example, triallyl isocyanurate (TAIC), triallyl cyanurate, diallyl phthalate, diallyl fumarate, and diallyl maleate can be cited. As poly(meth)acryloyloxy compounds, for example, trimethylolpropane trimethacrylate (TMPT), trimethylolpropane triacrylate (TMPTA), ethylene glycol diacrylate, ethylene glycol dimethacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, and 1,9-nonanediol diacrylate can be cited. As epoxy compounds, for example, epoxy compounds containing double bonds and epoxy groups, and epoxy compounds containing more than two epoxy groups can be cited. As epoxy compounds containing double bonds and epoxy groups, for example, glycidyl methacrylate and 4-hydroxybutyl acrylate glycidyl ether can be cited. Examples of epoxy compounds containing two or more epoxy groups include 1,6-hexanediol diglycidyl ether, 1,4-butanediol diglycidyl ether, cyclohexanedimethanol diglycidyl ether, and trimethylolpropane polyglycidyl ether. The crosslinking aid may be used alone or in combination of two or more.
[0075] Among them, triallyl isocyanurate (TAIC) is preferably used as a crosslinking aid. Triallyl isocyanurate (TAIC) has good compatibility with linear low-density polyethylene and can reduce crystallinity and maintain transparency through crosslinking. In addition, triallyl isocyanurate (TAIC) can impart flexibility at low temperatures to the protective layer.
[0076] The content of the crosslinking aid in the resin composition used for forming the protective layer can be appropriately selected depending on the target crosslinking degree and the like.
[0077] The content of the polyolefin-based resin is, for example, preferably 90 parts by mass or more, more preferably 95 parts by mass or more, based on 100 parts by mass of all resin components contained in the protective layer. This can improve transparency and flexibility.
[0078] Here, the ratio of the resin component contained in the protective layer can be analyzed based on the peak ratio detected by differential scanning calorimetry (DSC).
[0079] (b) Additives The protective layer may contain additives as required, such as light stabilizers, ultraviolet absorbers, antioxidants, heat stabilizers, nucleating agents, dispersants, leveling agents, plasticizers, defoamers, flame retardants, and fillers.
[0080] As a light stabilizer, for example, hindered amine light stabilizer (HALS) can be cited. Among hindered amine light stabilizers, according to the bond of the nitrogen atom in the piperidine skeleton, there are three types: N-H type (hydrogen is bonded to the nitrogen atom), N-R type (alkyl (R) is bonded to the nitrogen atom), and N-OR type (alkoxy (OR) is bonded to the nitrogen atom). Among them, the N-OR type hindered amine light stabilizer is preferred. The N-OR type is faster than the N-H type and the N-R type in terms of the speed of capturing free radicals. And the low molecular weight HALS of the N-OR type, which moves to the surface faster than the high molecular weight HALS, captures free radicals in a shorter time compared with the N-H type and the N-CH3 type HALS. Therefore, the degradation of the protective layer can be suppressed.
[0081] The above-mentioned weathering agents such as light stabilizers, ultraviolet absorbers and antioxidants can be added to the resin composition as a weathering masterbatch dispersed in the resin. The weathering masterbatch can be appropriately adjusted. On the other hand, commercial products can also be used. The resin used in the weathering masterbatch can be the above-mentioned polyolefin resin or other resins.
[0082] The content of the additive in the protective layer is, for example, 5 mass % or less.
[0083] (2) Physical properties of the protective layer When the protective layer contains a cross-linked polyolefin-based resin or a non-cross-linked polyolefin-based resin as described above, the degree of cross-linking can be represented by the gel fraction.
[0084] When the protective layer contains a non-crosslinked polyolefin-based resin, the gel fraction of the protective layer is usually 5% or less, preferably 0%.
[0085] On the other hand, when the protective layer contains a cross-linked polyolefin resin, the lower limit of the gel fraction of the protective layer is preferably 50% or more, more preferably 60% or more, for example. The upper limit of the gel fraction of the protective layer is preferably 90% or less, more preferably 80% or less. This is because if the above range is not satisfied, problems may arise in terms of heat resistance.
[0086] Here, in this specification, the gel fraction (%) can be measured by the following method. First, add 1.0 g of the protective layer to a resin sieve and extract it with 110°C xylene for 24 hours. Then, take it out together with the resin sieve, dry it, and weigh it. Then, compare the mass before and after extraction, and measure the mass % of the remaining insoluble component. And, the mass % of the remaining insoluble component is taken as the gel fraction.
[0087] In addition, a gel fraction of 0% means that the residual insoluble components are substantially 0 and the crosslinking reaction of the resin composition has not substantially started. More specifically, a gel fraction of 0% means that the residual insoluble components are completely absent and the mass % of the residual insoluble components measured by a precision balance is less than 0.05 mass %.
[0088] In addition, the above-mentioned residual insoluble components do not contain pigment components other than the resin components. When impurities other than these resin components are mixed in the residual insoluble components due to the above-mentioned test, for example, by separately measuring the content of these impurities in the resin components in advance, the gel fraction that should have been obtained can be calculated for the residual insoluble components from the resin components other than these impurities.
[0089] (3) Thickness of protective layer The thickness of the protective layer is not particularly limited as long as a protective film that satisfies the above-mentioned physical properties can be obtained. The thickness of the protective layer is, for example, preferably from 50 μm to 700 μm, more preferably from 80 μm to 600 μm, and further preferably from 100 μm to 500 μm. When the thickness of the protective layer is above a specified value, sufficient corrosion resistance can be obtained. In addition, by making the thickness of the protective layer below a specified value, the above-mentioned spring constant of the protective film is easily below a specified value. Therefore, the protective film can be easily stretched, and the adhesion and tracking properties to concave-convex and curved surfaces can be improved. In addition, when the thickness of the protective layer is below a specified value, sufficient transparency can be ensured.
[0090] (4) Method for forming a protective layer The protective layer can be obtained, for example, by mixing the above-mentioned components to prepare a resin composition, and then melting the resin composition to form a film in a sheet form. In addition, a crosslinking treatment may be performed after film formation.
[0091] As a method for mixing the components, for example, a method of impregnating the components in a polyolefin resin by dry blending can be cited. In addition, when the protective layer is obtained by extrusion molding, the crosslinking agent and the crosslinking aid can be added to the polyolefin resin in a liquid state. In addition, the crosslinking aid can also be pre-mixed in the polyolefin resin to prepare a mixture for use as a masterbatch component. When a masterbatch is used, the dispersibility of the crosslinking aid becomes better.
[0092] As the melt molding method, any common molding method may be used, for example, injection molding, extrusion molding, blow molding, compression molding, rotational molding, etc. may be mentioned. The molding temperature may be any temperature exceeding the melting point of the resin composition. In addition, the molding temperature may be set to a temperature at which crosslinking does not start during film formation, that is, a temperature at which the gel fraction of the resin composition can be maintained at 0%, depending on the crosslinking agent. The molding temperature is, for example, 80°C or more and 250°C or less.
[0093] As described above, examples of the cross-linking treatment include a cross-linking treatment using a cross-linking agent and a cross-linking treatment by irradiation with ionizing radiation.
[0094] The surface of the protective layer opposite to the adhesive layer may be subjected to an easy-adhesion treatment as required, which can improve the adhesion with the surface layer or the primer layer. Examples of easy-adhesion treatments include corona discharge treatment, plasma treatment, and ozone treatment.
[0095] 3. Adhesive layer The adhesive layer in the present invention is a member for attaching the protective film to a structure.
[0096] As the adhesive layer, there is no particular limitation as long as the protective film can be attached to the structure, and it can be appropriately selected according to the material of the structure. Common adhesives can be used in the adhesive layer. For example, ultraviolet curing adhesives, two-component curing adhesives, and pressure-sensitive adhesives can be listed. As pressure-sensitive adhesives, for example, acrylic adhesives, polyurethane adhesives, and silicone adhesives can be listed. Among them, acrylic adhesives are preferred. Acrylic adhesives have good transparency, weather resistance, heat resistance, etc.
[0097] The thickness of the adhesive layer is not particularly limited as long as the protective film can be bonded to the structure, and can be appropriately selected according to the application. The thickness of the adhesive layer is, for example, 25 μm to 120 μm, 25 μm to 90 μm, or 30 μm to 80 μm.
[0098] 4. Surface layer The protective film of the present invention is, for example, Figure 2As shown, it is preferred that the protective layer 1 has a surface layer 3 containing a cured product of an electron beam curable resin composition on the surface opposite to the adhesive layer 2. The protective film having the surface layer can further improve durability.
[0099] (1) Surface layer material (a) Electron beam curable resin The electron beam curable resin composition contains at least an electron beam curable resin. As the electron beam curable resin, one appropriately selected from polymerizable monomers, polymerizable oligomers, and polymerizable prepolymers can be used.
[0100] The polymerizable monomer is preferably a (meth)acrylate monomer having a free radical polymerizable unsaturated group in the molecule, among which a multifunctional (meth)acrylate is more preferred. In addition, (meth)acrylate refers to acrylate or methacrylate. The multifunctional (meth)acrylate is not particularly limited as long as it is a (meth)acrylate having two or more ethylenically unsaturated bonds in the molecule. Specifically, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, dicyclopentyl di(meth)acrylate, caprolactone-modified dicyclopentene di(meth)acrylate, ethylene oxide-modified phosphoric acid di(meth)acrylate, allylated cyclohexyl di(meth)acrylate, isocyanurate di(meth)acrylate can be listed. , trimethylolpropane tri(meth)acrylate, ethylene oxide-modified trimethylolpropane tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, propionic acid-modified dipentaerythritol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, propylene oxide-modified trimethylolpropane tri(meth)acrylate, tri(acryloyloxyethyl)isocyanate, propionic acid-modified dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ethylene oxide-modified dipentaerythritol hexa(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate. These multifunctional (meth)acrylates may be used alone or in combination of two or more.
[0101] In addition, in order to reduce the viscosity, etc., a monofunctional (meth)acrylate can be appropriately used in combination with the above-mentioned multifunctional (meth)acrylate within the range that does not impair the purpose of the present invention. Examples of the monofunctional (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, and isobornyl (meth)acrylate. These monofunctional (meth)acrylates can be used alone or in combination of two or more.
[0102] As polymerizable oligomers, for example, oligomers having free radical polymerizable unsaturated groups in the molecule can be cited. Specifically, epoxy (meth) acrylate system, polyurethane (meth) acrylate system, polyester (meth) acrylate system, polyether (meth) acrylate system, etc. can be cited. Here, epoxy (meth) acrylate oligomers can be obtained by, for example, reacting (meth) acrylic acid with the oxirane ring of a bisphenol epoxy resin or a varnish epoxy resin with a relatively low molecular weight and esterifying. In addition, carboxyl-modified epoxy (meth) acrylate oligomers obtained by partially modifying the epoxy (meth) acrylate oligomer with a dibasic carboxylic acid anhydride can also be used. Polyurethane (meth) acrylate oligomers can be obtained by, for example, esterifying polyurethane oligomers obtained by reacting polyether polyols, polyester polyols and polyisocyanates with (meth) acrylic acid. The polyester (meth)acrylate oligomer can be obtained, for example, by esterifying the hydroxyl groups of a polyester oligomer having hydroxyl groups at both ends obtained by condensation of a polycarboxylic acid and a polyol with (meth)acrylic acid. Alternatively, the polyester (meth)acrylate oligomer can be obtained, for example, by esterifying the hydroxyl groups at the ends of an oligomer obtained by adding oxyalkylene to a polycarboxylic acid with (meth)acrylic acid. The polyether (meth)acrylate oligomer can be obtained by esterifying the hydroxyl groups of a polyether polyol with (meth)acrylic acid.
[0103] In addition, as polymerizable oligomers, for example, polybutadiene (meth)acrylate oligomers with high hydrophobicity having (meth)acrylate groups in the side chains of polybutadiene oligomers, silicone (meth)acrylate oligomers having polysiloxane bonds in the main chains, aminoplast resin (meth)acrylate oligomers obtained by modifying aminoplast resins having a large number of reactive groups in small molecules, oligomers having cationically polymerizable functional groups in the molecules, etc. As oligomers having cationically polymerizable functional groups in the molecules, for example, varnish-type epoxy resins, bisphenol-type epoxy resins, aliphatic vinyl ethers, and aromatic vinyl ethers can be cited.
[0104] (b) Ultraviolet light absorber The surface layer may include a UV absorber. As described later, when a primer layer is not configured between the protective layer and the surface layer, the surface layer preferably includes a UV absorber. On the other hand, when a primer layer is configured between the protective layer and the surface layer, at least one layer preferably includes a UV absorber between the surface layer and the primer layer.
[0105] The ultraviolet absorber may be any of an inorganic ultraviolet absorber and an organic ultraviolet absorber.
[0106] As the inorganic ultraviolet absorber, for example, titanium oxide, cerium oxide, and zinc oxide having an average particle diameter of about 5 nm to 120 nm are preferable.
[0107] Examples of organic ultraviolet absorbers include benzotriazole ultraviolet absorbers, triazine ultraviolet absorbers, benzophenone ultraviolet absorbers, salicylate ultraviolet absorbers, and acrylonitrile ultraviolet absorbers. Examples of benzotriazole ultraviolet absorbers include 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-amylphenyl)benzotriazole, and 3-[3-(benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl]propionate of polyethylene glycol. Examples of the triazine-based ultraviolet absorber include 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]phenol, 1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and 1,3,5-tris[[3,5-bis-(1,1-dimethylethyl)-4-hydroxyphenyl]methyl].
[0108] Among them, triazine-based ultraviolet absorbers are preferred. Triazine-based ultraviolet absorbers have high ultraviolet absorption capacity and are less likely to be degraded by high energy such as ultraviolet rays.
[0109] In particular, the triazine-based ultraviolet absorber is preferably a hydroxyphenyltriazine compound represented by the following general formula (I).
[0110] The lower limit of the content of the ultraviolet absorber in the electron beam curable resin composition is preferably, for example, 0.01 parts by mass or more relative to 100 parts by mass of the electron beam curable resin. The upper limit of the content of the ultraviolet absorber in the electron beam curable resin composition is preferably, for example, 20 parts by mass or less, more preferably 15 parts by mass or less relative to 100 parts by mass of the electron beam curable resin. When the content of the ultraviolet absorber is too little, sufficient weather resistance may not be exerted. On the other hand, when the content of the ultraviolet absorber is too much, the ultraviolet absorber may ooze out. In addition, when the content of the ultraviolet absorber is too much, the curing of the electron beam curable resin may be inhibited.
[0111] (c) Other additives The surface layer may contain additives other than the ultraviolet absorber as necessary.
[0112] In order to impart weather resistance to the protective layer, a light stabilizer may be used together with the ultraviolet absorber. As the light stabilizer, for example, a hindered amine light stabilizer may be mentioned. Specifically, 2-(3,5-di-tert-butyl-4-hydroxybenzyl)-2'-n-butylmalonic acid bis(1,2,2,6,6-pentamethyl-4-piperidyl), bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate, tetrakis(2,2,6,6-tetramethyl-4-piperidyl)-1,2,3,4-butanetetracarboxylate, etc. may be mentioned.
[0113] In addition, the surface layer preferably contains calcined kaolin particles. By containing calcined kaolin particles in the surface layer, the marring resistance of the protective film is improved. Here, marring refers to small scratches that occur when the surface of the protective film is rubbed. In addition, excellent marring resistance means that scratches are not easily generated.
[0114] Examples of other additives include abrasion resistance improvers, polymerization inhibitors, crosslinking agents, infrared absorbers, antistatic agents, adhesion improvers, leveling agents, thixotropy imparting agents, coupling agents, plasticizers, defoamers, fillers, solvents, and colorants.
[0115] As the wear resistance improver, for example, it can be an inorganic substance or an organic substance. As the inorganic substance, for example, spherical particles of α-alumina, silica, kaolinite, iron oxide, diamond, silicon carbide, etc. can be listed. The shape of the particles is not particularly limited, and spheres, ellipsoids, polyhedrons, scales, etc. can be listed. Among them, spherical is preferred. As the organic substance, for example, resin beads of cross-linked acrylic resin, polycarbonate resin, etc. can be listed. The particle size of the spherical particles and resin beads is generally more than 30% and less than 200% of the thickness of the surface layer. Among them, spherical α-alumina is preferred. Spherical α-alumina has a high hardness and has a great effect on improving wear resistance. In addition, spherical particles are relatively easy to obtain.
[0116] As the polymerization inhibitor, for example, hydroquinone, p-benzoquinone, hydroquinone monomethyl ether, pyrogallol, tert-butylcatechol can be cited. As the cross-linking agent, for example, polyisocyanate compounds, epoxy compounds, metal chelate compounds, aziridine compounds, oxazoline compounds can be cited. As the filler, for example, barium sulfate, talc, clay, calcium carbonate, aluminum hydroxide can be cited. As the colorant, for example, quinacridone red, isoindolinone yellow, phthalocyanine blue, phthalocyanine green, titanium oxide, carbon black pigments can be cited. As the infrared absorber, for example, dithiol metal complexes, phthalocyanine compounds, diimmonium compounds can be cited.
[0117] (2) Thickness of the surface layer The lower limit of the thickness of the surface layer is, for example, 1 μm or more, and may be 2 μm or more. The upper limit of the thickness of the surface layer is, for example, 20 μm or less. When the thickness of the surface layer is too thin, the desired effect may not be obtained. In addition, when the thickness of the surface layer is too thick, the above-mentioned spring constant of the protective film may become larger.
[0118] (3) Method for forming the surface layer As a method for forming the surface layer, there is a method of applying an electron beam curable resin composition on the protective layer and curing it by irradiating it with electron beams.
[0119] As the coating method, a common method can be applied, and examples thereof include gravure coating, bar coating, roll coating, reverse roll coating, and comma coating. Among them, gravure coating is preferred.
[0120] When irradiating electron beams, the acceleration voltage can be appropriately selected according to the thickness of the coating film of the electron beam curable resin or electron beam curable resin composition used. The acceleration voltage is usually 70kV or more and 300kV or less. In addition, in the irradiation of electron beams, the higher the acceleration voltage, the more the penetration ability increases. Therefore, it is preferred to set the acceleration voltage in a manner that the penetration depth of the electron beam is substantially equal to the thickness of the surface layer. It is possible to suppress the irradiation of the protective layer with unnecessary electron beams.
[0121] In addition, the irradiation dose is preferably an amount that saturates the crosslinking density of the surface layer. The lower limit of the irradiation dose is usually 5 kGy or more, preferably 10 kGy or more. The upper limit of the irradiation dose is usually 300 kGy or less, preferably 50 kGy or less.
[0122] The electron beam source is not particularly limited, and various electron beam accelerators such as Cockcroft-Walton type, Van de Graft type, resonance transformer type, insulating core transformer type, linear type, dynamite type, and high frequency type can be used.
[0123] 5. Base coating The protective film of the present invention may have a primer layer between the protective layer and the surface layer, so as to improve the adhesion between the protective layer and the surface layer.
[0124] The material of the primer layer is not particularly limited as long as it can improve the adhesion of the protective layer and the surface layer. Among them, from the aspect of adhesion, polyurethane resin is preferred. As the polyurethane resin, for example, a two-component curable polyurethane resin can be used. In the two-component curable polyurethane resin, as a polyol component, an acrylic acid-polyurethane block copolymer is preferably used. In addition, in the two-component curable polyurethane resin, from the aspect of light resistance adhesion, as an isocyanate component, aliphatic isocyanate or alicyclic isocyanate is preferably used.
[0125] In the acrylic-polyurethane block copolymer, it is also preferable to use an aliphatic isocyanate or an alicyclic isocyanate as the isocyanate component in the polyurethane portion from the viewpoint of light-resistant adhesion. Alternatively, an alicyclic isocyanate and an aliphatic isocyanate may be used in combination.
[0126] Examples of the alicyclic isocyanate include IPDI (isophorone diisocyanate) and hydrogenated MDI (hydrogenated diphenylmethane diisocyanate), and examples of the aliphatic isocyanate include 1,6-hexamethylene diisocyanate and 2,2,4-trimethylhexamethylene diisocyanate.
[0127] The acrylic-polyurethane block copolymer is a copolymer of two blocks including an acrylic polymer part and a polyurethane polymer part. By including the acrylic copolymer part, when an acrylate-based electron beam curable resin is used in the surface layer, the adhesion between the surface layer and the primer layer is improved. In addition, by including the polyurethane polymer part, the adhesion between the surface layer and the primer layer can also be improved. In particular, the adhesion between the protective layer using the polyurethane acrylate-based electron beam curable resin and the primer layer is improved.
[0128] The acrylic-polyurethane block copolymer, for example, comprises: (a) a hydroxyl-containing acrylic copolymer component containing an acrylic monomer in the main chain and having a hydroxyl group at the terminal and / or side chain, (b) a polyester polyurethane polymer component or a polyether polyurethane polymer component, and (c) a reaction product of a diisocyanate. The copolymer is obtained by reacting the three components to produce a prepolymer, and further reacting the prepolymer with a chain extender such as a diamine to extend the chain.
[0129] The polyester polyurethane polymer component and the polyether polyurethane polymer component of (b) above may be used alone or in combination. In addition, as the polyester polyurethane polymer component, a polymer obtained by: (1) adding a diamine compound to a polyester polyol component to urea-formulate a portion of the polyurethane skeleton, (2) introducing a phenyl group into the polyester polyol component, (3) adding a diamine compound to a polyester polyol component whose alcohol component is a polycarbonate-based component to urea-formulate a portion of the polyurethane skeleton, etc. may also be used. In the acrylic-polyurethane block copolymer, the ratio of the acrylic copolymer component to the polyurethane polymer component may be appropriately adjusted, and is preferably 40 / 60 to 60 / 40 in terms of mass ratio from the perspective of good adhesion.
[0130] In addition, as the polyurethane polymer component, thermoplastic polyurethane resin can also be used. Thermoplastic polyurethane resin is a resin obtained by reacting diisocyanate, high molecular weight polyol, and low molecular weight diols as required. In addition, in high molecular weight polyol, high molecular weight is a term relative to low molecular weight multifunctional active hydrogen compounds, and also includes polyols with molecular weights lower than 10,000.
[0131] As the diisocyanate used in the thermoplastic polyurethane resin, for example, aromatic diisocyanates, aliphatic diisocyanates, and alicyclic diisocyanates can be cited. As aromatic diisocyanates, for example, 4,4′-diphenylmethane diisocyanate (MDI), 2,4-toluene diisocyanate, 1,5-naphthalene diisocyanate, orthoisocyanate benzenesulfonyl isocyanate, metaisocyanate benzenesulfonyl isocyanate, or paraisocyanate benzenesulfonyl isocyanate can be cited. As aliphatic diisocyanates, for example, 1,6-hexamethylene diisocyanate can be cited. As alicyclic diisocyanates, for example, isophorone diisocyanate (IPDI), hydrogenated xylene diisocyanate, and hydrogenated diphenylmethane diisocyanate can be cited. Polymers or adducts of these diisocyanates can also be used. In addition, these diisocyanates can be used alone or in combination of two or more.
[0132] As the high molecular weight polyol used for the thermoplastic polyurethane resin, polyester polyol, polyether polyol, etc. can be listed. These can be used alone or in combination of two or more. Among them, polyester polyol is preferred from the perspective of weather resistance and adhesion.
[0133] As polyester polyols, for example, condensed polyester diols obtained by reacting low molecular weight diols with dicarboxylic acids, polylactone diols obtained by ring-opening polymerization of lactones, polycarbonate diols, etc. can be cited. As dicarboxylic acids, aliphatic dicarboxylic acids, aromatic dicarboxylic acids, etc. can be cited. As aliphatic dicarboxylic acids, succinic acid, adipic acid, sebacic acid, glutaric acid, azelaic acid, maleic acid, fumaric acid, etc. can be cited. As aromatic dicarboxylic acids, terephthalic acid, isophthalic acid, etc. can be cited. Dicarboxylic acids can be used alone or in combination of two or more. In addition, as lactones, ε-caprolactone, etc. can be cited.
[0134] Specific examples of the polyester polyol include polyethylene adipate, polybutylene adipate, polyhexamethylene adipate, polyneopentyl adipate, polyethylene butylene adipate, polybutylene hexabutylene adipate, polyethylene diethylene adipate, polytetramethylene adipate, polyethylene azelaic acid, polyethylene sebacate, polybutylene azelaic acid, polybutylene sebacate, and polyhexamethylene carbonate diol. These may be used alone or in combination of two or more.
[0135] As low molecular diols used for thermoplastic polyurethane resin, for example, ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, neopentyl glycol, 1,6-hexanediol, etc. can be listed. In addition, low molecular diols having cyclic groups such as bis(hydroxymethyl)cyclohexane, m-xylene glycol or p-xylene glycol, bis(hydroxymethyl)benzene, 1,4-bis(2-hydroxyethoxy)benzene, 4,4-bis(2-hydroxyethoxy)-diphenylpropane (ethylene oxide adduct of bisphenol A) can also be listed. These can be used alone or in combination of two or more.
[0136] The thickness of the primer layer varies depending on the intended use, but is, for example, 1 μm to 10 μm.
[0137] The method for forming the primer layer may be a method of coating the primer layer resin composition on the protective layer. A common method may be used as the coating method, and an example thereof may be a roll coating method.
[0138] 6. Other structures The protective film of the present invention may have other structures depending on the application.
[0139] The protective film of the present invention may have a separator on the surface of the adhesive layer opposite to the protective layer.
[0140] 7. Purpose The protective film in the present invention can be used by sticking on the surface of a structure, for example. In addition, the surface of the structure to which the protective film is to be stuck can be a flat surface or a curved surface. In addition, the structure is described below.
[0141] B. Structures The structure in the present invention may have the above-mentioned protective film.
[0142] The structure is preferably a structure arranged outdoors or a structure used outdoors. Examples of the structure arranged outdoors include windmills, lightning rods, antennas, antenna covers, and pipes of wind power generation devices. Examples of pipes include pipelines, exhaust pipes, water pipes, and electric wire pipes. In addition, examples of the structure used outdoors include frames or parts of moving bodies. Examples of moving bodies include cars, railway vehicles, aircraft, and bicycles. Examples of cars include passenger cars, trucks, and buses. Examples of railway vehicles include trams, Shinkansen, and locomotives. Examples of aircraft include airplanes, helicopters, and drones.
[0143] Among them, the structure is preferably a windmill of a wind power generation device. The windmill is composed of blades, a nacelle, a hub and a tower. In particular, it is preferred to stick a protective film on the surface of the windmill blades.
[0144] As mentioned above, the blades of the wind turbine of the wind turbine are exposed to a harsh environment. In addition, due to the high-speed rotation of the blades, there is a high possibility of damage, deformation, surface contamination, and surface peeling. These adverse conditions lead to a decrease in power generation efficiency. In the worst case, the blades may break or fall off. Therefore, it is preferable to configure a protective film on the surface of the blades of the wind turbine of the wind turbine.
[0145] Furthermore, when a protective film is disposed on the surface of a moving object, the protective film can be used as a packaging film, for example.
[0146] The protective film may be disposed on a part of the surface of the structure, or may be disposed on the entire surface of the structure.
[0147] The present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are examples, and any configuration substantially the same as the technical concept described in the scope of the claims of the present invention and any configuration having the same function and effect are included in the technical scope of the present invention.
[0148] Example Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples.
[0149] [Example 1] (1) Formation of protective layer The following weathering agent masterbatch was mixed at a ratio of 5 parts by mass with respect to 95 parts by mass of the following base resin to prepare a resin composition.
[0150] Base resin: density 0.901g / cm 3 , a metallocene linear low-density polyethylene resin (M-LLDPE) having a melting point of 93°C and an MFR of 2.0 g / 10 minutes at 190°C.
[0151] Weathering agent masterbatch: density is 0.880g / cm 3 , 100 parts by mass of a low-density polyethylene resin having an MFR of 3.5 g / 10 minutes at 190° C., 0.6 parts by mass of HALS (“KEMISTAB 62” manufactured by CHEMIPRO KASEI), 3.5 parts by mass of an ultraviolet absorber 1 (“KEMISORB 12” manufactured by CHEMIPRO KASEI), and 0.6 parts by mass of an ultraviolet absorber 2 (“KEMISORB 79” manufactured by CHEMIPRO KASEI).
[0152] The above-mentioned MFR is a value measured by the method described in the column of “2. Protective layer (1) Material of protective layer (a) Polyolefin resin”.
[0153] The resin composition was formed into a sheet using a film forming machine having a φ30 mm extruder and a T-die with a width of 200 mm at an extrusion temperature of 210° C. to form a protective layer with a thickness of 300 μm. In addition, the pulling speed was adjusted to obtain a specified thickness. In addition, as for the cooling roller and rubber roller directly below the T-die, a chrome-plated cooling roller with a surface roughness of Rz1.5 μm was used for the cooling roller, and a silicone rubber roller with a hardness of 70 degrees was used for the rubber roller.
[0154] (2) Formation of adhesive layer The following components were blended to prepare an adhesive composition.
[0155] Adhesive: 100 parts by mass of an alkyl (meth)acrylate copolymer (Nissetsu KP-2680 manufactured by NIPPON CARBIDE INDUSTRIES CO., INC., solid content concentration: 45% by mass, solvent: methyl ethyl ketone).
[0156] Cross-linking agent: 0.2 parts by mass of an isocyanate group-terminated polyurethane resin (Nissetsu CK-121 manufactured by NIPPON CARBIDE INDUSTRIES CO., INC., solid content concentration: 10% by mass, solvent: methyl ethyl ketone).
[0157] Silane coupling agent (“KBM-403” manufactured by Shin-Etsu Chemical Co., Ltd., solid content concentration: 100% by mass) 0.23 parts by mass
[0158] 0.57 parts by mass of a phenolic antioxidant ("ADEKASTUB AO-60G" manufactured by ADEKA Corporation, solid content concentration: 100% by mass).
[0159] 0.57 parts by mass of ultraviolet absorber ("ADEKASTUB LA-24" manufactured by ADEKA Corporation, solid content concentration: 100% by mass)
[0160] Next, the adhesive composition was applied to the release-treated surface of a 50 μm thick PET separator (“PET50x1-J2” manufactured by NIPPA) so that the thickness after drying was 60 μm, and dried to form an adhesive layer. Thereafter, the laminate of the separator and the adhesive layer was laminated on one surface of the protective layer and stored at 50° C. for 3 days. Thus, a protective film was obtained.
[0161] [Example 2] A protective film was produced in the same manner as in Example 1 except that the thickness of the protective layer was set to 150 μm.
[0162] [Example 3] A protective film was produced in the same manner as in Example 1 except that 5 parts by mass of the weathering agent masterbatch used in Example 1 was mixed with 95 parts by mass of the following base resin to prepare a resin composition.
[0163] Base resin: density 0.887g / cm 3 , a metallocene linear low-density polyethylene resin (M-LLDPE) having a melting point of 119°C and an MFR of 5.0 g / 10 minutes at 190°C.
[0164] [Example 4] A protective film was produced in the same manner as in Example 3 except that the thickness of the protective layer was set to 150 μm.
[0165] [Example 5] A protective layer was formed in the same manner as in Example 1. Next, a 5 g / m 2 The following electron beam curable resin composition was applied, and electron beams were irradiated at an acceleration voltage of 125 kV and an irradiation dose of 50 kGy (5 Mrad) to cure the electron beam curable resin composition, thereby forming a surface layer.
[0166] Electron beam curable resin composition: 20 parts by mass of silica particles having an average particle size of 5 μm and 3 parts by mass of a UV absorber (a compound represented by the above general formula (I), “Tinuvin 479” manufactured by BASF Japan) were added to 100 parts by mass of urethane acrylate to prepare an electron beam curable resin composition.
[0167] Next, in the same manner as in Example 1, an adhesive layer was formed on the separator, and the laminate of the separator and the adhesive layer was laminated on the other surface of the protective layer, and stored at 50° C. for 3 days. Thus, a protective film was obtained.
[0168] [Example 6] A protective film was produced in the same manner as in Example 5 except that the thickness of the protective layer was set to 150 μm.
[0169] [Example 7] A protective layer was formed in the same manner as in Example 1. Next, a 1.5 g / m 2 The primer composition described below was applied to form a primer layer.
[0170] Primer composition: 16 parts by mass of a UV absorber (a compound represented by the above general formula (I), “Tinuvin 479” manufactured by BASF Japan) was added to 100 parts by mass of a two-component curable acrylic-urethane resin to prepare a primer composition.
[0171] Next, a surface layer was formed on the primer layer in the same manner as in Example 5. Next, an adhesive layer was formed on the separator in the same manner as in Example 1, and the laminate of the separator and the adhesive layer was laminated on the other side of the protective layer and stored at 50° C. for 3 days. Thus, a protective film was obtained.
[0172] [Example 8] A protective film was produced in the same manner as in Example 7 except that the thickness of the protective layer was set to 150 μm.
[0173] [Comparative Example 1] 70 g of water-dispersible polycarbonate polyurethane A (cyclohexane skeleton content: about 36% by mass), 0.85 g of Tinuvin 1130 (manufactured by BASF JAPAN, UV absorber), 0.5 g of Tinuvin 292 (manufactured by BASF JAPAN, light stabilizer), 0.2 g of Triton GR-7M (manufactured by Dow Chemical, surfactant), 0.1 g of AMP95 (manufactured by ANGUS Chemical Company, neutralizer), and 3 g of deionized water were mixed and stirred to prepare a pre-solution. The pre-solution was bar-coated on a PET film, dried at 90°C for 3 minutes in a hot air oven, and then further dried and cured at 160°C for 3 minutes. Thus, a protective layer with a thickness of 300 μm was formed.
[0174] Next, in the same manner as in Example 1, an adhesive layer was formed on the separator, and the laminate of the separator and the adhesive layer was laminated on the surface of the protective layer opposite to the PET film, and stored at 50° C. for 3 days. Thus, a protective film was obtained.
[0175] [Comparative Example 2] A protective film was produced in the same manner as in Example 1 except that 5 parts by mass of the weathering agent masterbatch used in Example 1 was mixed with 95 parts by mass of the following base resin to prepare a resin composition.
[0176] Base resin: density 1.15g / cm 3 , polyurethane resin with a glass transition temperature of -25°C.
[0177] [Comparative Example 3] The protective layer was formed in the same manner as in Comparative Example 2 except that the thickness of the protective layer was set to 150 μm. Next, a surface layer was formed on one surface of the protective layer in the same manner as in Example 5. Next, an adhesive layer was formed on the separator in the same manner as in Example 1, and the laminate of the separator and the adhesive layer was laminated on the other surface of the protective layer and stored at 50° C. for 3 days. Thus, a protective film was obtained.
[0178] [evaluate] (1) Spring constant at 10% elongation A tensile tester "Tensilon RTF1150" manufactured by A & D was used as a tensile tester, and the protective film was subjected to a tensile test under the following conditions in accordance with ISO 527-3:2018. The tensile load and elongation at 10% elongation were measured to determine the spring constant at 10% elongation. In addition, the tensile test was performed after the separator was peeled off from the protective film.
[0179] (Measurement conditions for tensile test) Test piece: long strip; Test piece size: width 10mm, length 120mm; Distance between fixtures: 100mm; Stretching speed: 50mm / min.
[0180] [Table 1] (2) Light resistance test As a weathering tester, an "EYE SUPER UV TESTER SUV-W151" manufactured by Iwasaki Electric Co., Ltd. was used, and the protective film was subjected to a radiant illuminance of 1000 W / m 2 , UV rays with a wavelength of 300 nm to 400 nm were irradiated at a blackboard temperature of 63°C. The blackboard temperature was set to 63±5°C. The irradiation time was set to 120 hours and 240 hours. In addition, as described above, the separator was peeled off from the protective film, and the ETFE film was attached, and then the light resistance test was performed.
[0181] (2-1) Maintenance rate of tensile failure stress As a tensile testing machine, for example, "Tensilon RTF1150" manufactured by A & D can be used. According to ISO527-3:2018, the tensile stress before and after the light resistance test is measured under the following conditions. In addition, the maintenance rate of the tensile stress after the light resistance test is calculated. In addition, before the light resistance test, the tensile test is performed after the separator is peeled off from the protective film. In addition, after the light resistance test, the tensile test is performed after the ETFE film is peeled off.
[0182] (Measurement conditions) Test piece: long strip; Test piece size: width 10mm, length 50mm; Distance between fixtures: 30mm; Stretching speed: 50mm / min.
[0183] [Table 2] (2-2) Yellowing Intensity (ΔYI) As a colorimeter, "CC-i" manufactured by Suga Test Instruments Co., Ltd. was used. The yellowness (YI) before and after the light resistance test was determined by the stimulus value direct reading method according to ISO17223:2014 under the following conditions. The yellowing degree (ΔYI) was also determined. In addition, the yellowness was measured after the separator was peeled off from the protective film before the light resistance test. In addition, the yellowness was measured after the ETFE film was peeled off after the light resistance test.
[0184] (Measurement conditions) Light source: C light source; Field of view:2°.
[0185] [Table 3] (2-3) Maintenance rate of elongation at breaking point As a tensile testing machine, "Tensilon RTF1150" manufactured by A & D was used, and the elongation at break before and after the light resistance test could be obtained under the following conditions according to ISO 527-3:2018. In addition, the maintenance rate of the elongation at break after the light resistance test was obtained. In addition, before the light resistance test, the tensile test was performed after the separator was peeled off from the protective film. In addition, after the light resistance test, the tensile test was performed after the ETFE film was peeled off.
[0186] (Measurement conditions) Test piece: long strip; Test piece size: width 10mm, length 50mm; Distance between fixtures: 30mm; Stretching speed: 50mm / min.
[0187] [Table 4] (3) High temperature and high humidity test The protective film was stored at a temperature of 85° C. and a humidity of 85% RH for 500 hours, 1000 hours, 1500 hours, or 2000 hours using a “high temperature and high humidity tank FX424C” manufactured by Kusumoto Chemicals Co., Ltd.
[0188] (3-1) Maintenance rate of tensile failure stress The maintenance rate of the tensile breaking stress after the high-temperature and high-humidity test was determined in the same manner as in the above (2-1).
[0189] [Table 5] (3-2) Yellowing Intensity (ΔYI) The yellowing degree (ΔYI) after the high-temperature and high-humidity test was determined in the same manner as in the above (2-2).
[0190] [Table 6] (3-3) Maintenance rate of elongation at breaking point The same operation as in the above (2-3) was performed to determine the maintenance rate of the elongation at break after the high-temperature and high-humidity test.
[0191] [Table 7] In Examples 1 to 8, since an olefin resin is used in the protective layer, the retention rate of the tensile stress after the prescribed light resistance test is higher than that of Comparative Examples 1 to 3 in which a polyurethane resin is used in the protective layer. In addition, in Examples 1 to 8, ΔYI after the prescribed light resistance test is smaller than that of Comparative Examples 2 to 3, and ΔYI after the prescribed high temperature and high humidity test is smaller than that of Comparative Examples 1 to 3.
[0192] In addition, when Examples 1 to 4 are compared with Examples 5 to 8, when the protective film further has a surface layer, the maintenance rate of the tensile stress after the prescribed light resistance test, the maintenance rate of the elongation at break after the prescribed light resistance test, the maintenance rate of the tensile stress after the prescribed high temperature and high humidity test, and the maintenance rate of the elongation at break after the prescribed high temperature and high humidity test become higher. Therefore, when the protective film further has a surface layer, it is confirmed that the durability is further improved.
[0193] The present invention provides the following [1] to [7].
[0194] [1] A protective film comprising a protective layer comprising a polyolefin resin and an adhesive layer disposed on one surface of the protective layer, wherein the value obtained by dividing the tensile load at 10% elongation by the elongation at 10% elongation is 3.0 N / mm or less.
[0195] [2] The protective film according to [1], wherein the 2 , when a light resistance test is performed for 240 hours using ultraviolet rays with a wavelength of 300nm to 400nm at a blackboard temperature of 63°C, the maintenance rate of the tensile breaking stress after the above light resistance test is 18% or more.
[0196] [3] The protective film according to [1] or [2], wherein the yellowing index (ΔYI) after the light resistance test is 10 or less.
[0197] [4] The protective film according to any one of [1] to [3], wherein when subjected to a high temperature and high humidity test at a temperature of 85° C. and a humidity of 85% RH for 2000 hours, the yellowing index (ΔYI) after the high temperature and high humidity test is 10 or less.
[0198] [5] The protective film according to any one of [1] to [4], wherein the protective layer has a surface layer containing a cured product of an electron beam-curable resin composition on a surface opposite to the adhesive layer.
[0199] [6] The protective film according to [5], further comprising a primer layer between the protective layer and the surface layer.
[0200] [7] A structure having the protective film according to any one of [1] to [6].
[0201] Explanation of symbols 1 ... protective layer; 2 ... adhesive layer; 3 ... surface layer; 10 ... protective film.
Claims
1. A protective film, characterized in that: The invention comprises a protective layer comprising a polyolefin resin and an adhesive layer disposed on one surface of the protective layer. The value obtained by dividing the tensile load at 10% elongation by the elongation at 10% elongation is 3.0 N / mm or less.
2. The protective film according to claim 1, characterized in that: The irradiance was 1000W / m 2 , when a light resistance test is performed under the condition of a black board temperature of 63° C. using ultraviolet rays with a wavelength of 300 nm to 400 nm for 240 hours, the maintenance rate of the tensile breaking stress after the light resistance test is 18% or more.
3. The protective film according to claim 1 or claim 2, characterized in that: The yellowing degree ΔYI after the light resistance test is 10 or less.
4. The protective film according to claim 1 or claim 2, characterized in that: When a high-temperature and high-humidity test is performed under conditions of a temperature of 85° C. and a humidity of 85% RH for 2000 hours, the yellowing degree ΔYI after the high-temperature and high-humidity test is 10 or less.
5. The protective film according to claim 1 or claim 2, characterized in that: The protective layer has a surface layer including a cured product of an electron beam-curable resin composition on a surface opposite to the adhesive layer.
6. The protective film according to claim 5, characterized in that: A primer layer is provided between the protective layer and the surface layer.
7. A structure, characterized in that: A protective film according to claim 1 or claim 2.
Citation Information
Patent Citations
Surface protective film, and multilayer film having the same
JP2010260942A
Blade and protective laminated sheet for blade
WO2012102294A1
Multilayer film, method for producing same and laminate
CN110099796A
Pressure-sensitive adhesive sheet
WO2021065595A1